Interactional Styles Used by Joy Mangano in 2015 Joy Movie - Jason Louis Susanto; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study was conducted to find out the interactional styles used in Joy Mangano’s utterances from the 2015 Joy movie, specifically when she was in negotiation scenes. This study used the theory of interactional styles by Holmes (2006) and supporting theory of negotiation by Lewicki et al. (2003). This study used a qualitative approach to analyze the data. The findings found that Joy Mangano was dominant to use more masculine interactional styles in the outcome of successful and unsuccessful negotiation scenes. This can happen because of specific reasons as mentioned in the findings and discussions of this study. The study expected more worthwhile and insightful research to find out whether particular configurations of either feminine or masculine interactional styles may definitely have something to contribute to the negotiation outcome.